СОВРЕМЕННЫЕ МЕТОДЫ ОБУЧЕНИЯ ТЕХНОЛОГИЯМ ШВЕЙНОГО ПРОИЗВОДСТВА В ЦИФРОВОЙ ОБРАЗОВАТЕЛЬНОЙ СРЕДЕ (Multidisciplinary Journal of Science and Technology, 2026)
In this state, a comprehensive analysis of modern methods of training is presented in the digital environment. Takje podcherkivaetsya vajnost information-communication technology and development of professional knowledge, skills and competence of students. Obsnovany vozmojnosti povysheniya effektivnosti obrazovaniya s pomoshchyu digital platform, automated design system (CAD) and interactive pedagogical approaches.